STRATEGI KOMUNIKASI PEMASARAN DALAM MEMBANGUN KESADARAN MEREK (Studi Kasus Private Label pada Fast Moving Consumer Goods Giant Ekstra Central Business District, Bintaro, Tangerang Selatan) - RACHMI KURNIA SIREGAR (Fakultas Ilmu Komunikasi - Universitas Budi Luhur, 2015)
Retail business related private label products in Indonesia continue racing with increasing needs and desires of consumers who crave quality products at low prices. One of them was intense Giant Ekstra offers a variety of private label products are oriented to customers. Related to this phenomenon, the study aims to examine the marketing communication strategy Giant Ekstra Central Business District (CBD) Bintaro, South Tangerang in building awareness of private label brands in the fast moving consumer goods (FMCG). This study used a retail communication mix of Levy & Weitz Retail (2009) includes communication tap-mouth (WOM), advertising, sales promotion and store atmosphere. Methods of research used a qualitative approach and case studies based on the conceptual framework of private label, fast moving consumer goods (FMCG), brand awareness and retail communications mix. The results of the study, the use of retail communications mix of Levy by Giant Ekstra indicated not make private label as a FMCG Giant Ekstra on top of brands and top of mind. Giant Ekstra advised continuously improve the quality of private label products with intense enhance performance such as WOM marketing communications, sales promotion, advertising and store atmosphere. And more aggressive in communicating private label products in the FMCG by activating the function of personal selling and direct marketing. Also create a database of customers, establish membership and customer communities.